Mean Arterial Pressure, Uterine Artery Doppler and Serum Placental Growth Factor Measured in First Trimester for Prediction of Preeclampsia: A Prospective Observational Study - K Geetha; Mamatha; Urvashi; MN Vanitha Gowda (Journal of Clinical and Diagnostic Research)
Introduction: Preeclampsia affects 2 to 5% of pregnant women and is a leading cause of maternal and perinatal morbidity and mortality. Aim: To predict the development of preeclampsia during the first trimester by using mean arterial pressure, uterine artery Doppler, and serum placental growth factor. Materials and Methods: A prospective observational study was conducted among women attending the Outpatient Department (OPD) for antenatal care at Ramaiah Medical College hospitals in Bengaluru, Karnataka, India from November 2018 to May 2020. A total of 80 antenatal participants, with singleton pregnancies between 11 and 13+6 weeks, underwent thorough examinations with appropriate investigations. Participants found to have a uterine artery Pulsatility Index (PI) >95th percentile were started on Tablet Aspirin 150 mg once a day. All study participants were followed until delivery to observe the development of preeclampsia and neonatal outcomes. Receiver Operating Characteristic (ROC) curve analysis was performed to determine the Area Under the Curve (AUC) for the three variables and their combination, and sensitivity, specificity, and diagnostic accuracy were determined. Statistical significance was set at p-value <0.05. Results: The mean age of the study participants was 26.54±3.14 years. During the study period, out of 80 women, 5 (6.25%) developed hypertensive disorders; among them, 2 (2.5%) had early-onset preeclampsia and 3 (3.75%) had gestational hypertension. Total 10 (12.5%) women had a uterine artery pulsatility index >95th percentile and were started on Tablet Aspirin 150 mg; among them, 3 (3.75%) developed hypertension and 7 (8.75%) did not. The combined mean arterial pressure, mean uterine artery pulsatility index, and placental growth factor had a sensitivity of 100%, specificity of 87%, Positive Predictive Value (PPV) of 33%, Negative Predictive Value (NPV) of 100%, and diagnostic accuracy of 88%. Conclusion: The first trimester combined assessment of mean arterial pressure, uterine artery Doppler, and serum placental growth factor has proven to be the best screening test for the early prediction of preeclampsia.